Morpho-agronomic variability of three kola trees accessions [Cola nitida (Vent.) Schott et Endl., Cola acuminata (P. Beauv.) Schott et Endl., and Garcinia kola Heckel] from Southern Benin - ADOUKONOU, AWO SAGBADJA HUBERT (My University, 2016)
Cola nitida, Cola acuminata and Garcinia kola are part of underutilized forest resources in Benin. The lack of information on these trees limits seriously the exploitation, regeneration and use of their genetic resources. This study aimed to evaluate the morphological diversity of these kola trees for a better management and rationale utilization of their genetic resources. For this purpose, 90 trees samples were characterized through 19 descriptors for G. kola, and 38 for both C. nitida and C. acuminata. An analysis of variance and a numerical classification followed by principal component analysis of quantitative data in addition to the descriptive analysis of the qualitative data were used to describe the inter and intra-specific diversity in these kola trees. The study revealed strong correlations (positive and negative) between the different variables. The morphometric data analysis revealed significant differences among trees of different kola species with the most discriminative traits related to the plant size and fruit parameters such as fruit length, fruit thickness and fruit weight. G. kola was the tallest species displaying the largest fruit thickness while C. acuminata and C. nitida had comparably the longest and most weighted fruits. Important intraspecific variability was also detected within kola species with C. acuminata showing the lowest diversity. Cluster analyses conducted separately on species data revealed clear phenotypic organization among the analyzed trees with seven clusters identified in C. nitida, five in G. kola and four in C. acuminata. This study provided useful information on the genetic variability of three kola species and is a preliminary base that could be used in a breeding program.
Keywords: Benin Characterization Cola nitida; Cola acuminata Diversity Fruit tree Garcinia; kola Kola tree Morphotype